Type 2N von Willebrand Disease: Rapid Genetic Diagnosis of G2811A (R854Q), C2696T (R816W), T2701A (H817Q) and G2823T (C858F) – Detection of a Novel Candidate Type 2N Mutation: C2810T (R854W) - Bowen, D. J.; Standen, G. R.; Mazurier, C.; Gaucher, C.; Cumming, A.; Keeney, S.; Bidwell, J. (Thrombosis and Haemostasis, 1998)
The majority of patients with type 2N von Willebrand disease (VWD type 2N) have mutations in the region of the von Willebrand factor (VWF) gene encoding the factor VIII binding domain of VWF. Two mutations predominate among VWD type 2N patients: G2811A and C2696T, which respectively bring about the amino acid substitutions R854Q and R816W in VWF. Several other mutations have been found in VWD type 2N, including T2701A (H817Q) and G2823T (C858F). We have developed a genetic test which permits rapid screening for these four mutations in a single polymerase chain reaction (PCR). The test employs induced heteroduplex formation using two universal heteroduplex generators, one of which detects G2811A (R854Q) and G2823T (C858F), the other detects C2696T (R816W) and T2701A (H817Q). The allele frequency of the common G2811A (R854Q) mutation was investigated in the local (S. Wales) population by examination of 216 VWF genes (108 individuals) and was found to be 0.01. The heteroduplex-based test additionally detected a novel candidate type 2N mutation, C2810T (R854W) and a previously described polymorphism, G2805A (R852Q). The polymorphism showed allele frequencies of 0.92 (G nucleotide) and 0.08 (A nucleotide) in the population study.